A study on the psychological functioning of children with specific learning difficulties and typically developing children - Nurul Shafira Adi; Azizah Othman; Kuay, Hue San; Qarem Mohamed Mustafa (BioMed Central Ltd, 2024)
Introduction Dyslexia is a widespread Specific Learning Difficulty, and children with dyslexia often face significant psychological difficulties due to their challenges with reading, spelling, and writing. Objective This study examines the psychological functioning of children with dyslexia and compares it with typically developing children. Method This cross-sectional study used the Child Behavior Checklist (CBCL) to evaluate behavioral issues and the State Trait Anxiety Inventory (STAI) to assess anxiety levels. Primary school teachers, who had known the children for at least a year, provided the reports. Data were analyzed using an independent sample t-test. Results Forty children with dyslexia (n=40) and fifty typically developing children (n=50) were assessed, in which both groups are predominantly boys (70%, 54%) aged 7–12 years (Mean age:9.3±1.5). The results indicate a significantly greater degree of behavioural problems t(88)=8.39,p<0.001 among children with dyslexia compared to typically developing children. They also had higher level of anxiety t(88)=6.81,p<0.001 compared to typically developing children. Conclusion The findings highlight a strong connection between emotional and behavioral issues in children with dyslexia. Generally, these children are more prone to depression, anxiety, and disruptive behaviors compared to their peers. The study underscores the importance of a multidisciplinary approach that integrates emotional needs assessment and management into the interventions for children with dyslexia.